Measuring the banking performance based on corporate social responsibility achievement: Decision support system adoption - O., Okfalisa; R., Habib; R., Hidayati; M., Mahyarni; Alex, W.; Nawanir, Gusman; S., Saktioto (AIP Publishing, 2021)
Corporate Social Responsibility (CSR) discloses the social responsibility of a company in contributing to the quality improvement of the community and society. Currently, the banking industries put into concern on this social responsibility as well as CSR report as environmental issues that leveraging the economic business performance through the application of the Global Reporting Initiatives (GRI) framework. The number of the organization using this framework has increased. Unfortunately, several weaknesses have been reviewed on the adoption of this framework as a sustainability report. Therefore, this study tried to strengthening the GRI model by elaborating on the indicators and sub-indicators of GRI-4 to measure the priority weighted-based indicators thus it is utilized to rank the banking performance. Herein, the decision support system-based analytical network process (ANP) is applied to assess standard criteria of the GRI sustainability report as a side of economic, social, and environmental aspects. Three banking companies in Indonesia have been selected as alternatives and then analyzed based on its sustainability report as well as performance measurement. Twenty-four experts from academicians and practices have been asked their quantitative perspectives and weighting score of the criteria through the dissemination of the questionnaire. This study reveals the performance of banking companies following the realization of the CSR position. Thus, the financial services authority of Indonesia (OJK) as an Indonesian government agency is advised on the decision-making on the potential banking performance that more pay attention to environmental sustainability. Besides, the employment of the ANP method in this study can strengthen and accomplish the shortcoming of the GRI model in determining the sustainability report.